Biochemical Evidence for Translational Repression by Arabidopsis MicroRNAs - Lanet, Elodie (American Society of Plant Biologists, 2009)
MicroRNAs (miRNAs) regulate gene expression posttranscriptionally through RNA silencing, a mechanism conserved in eukaryotes. Prevailing models entail most animal miRNAs affecting gene expression by blocking mRNA translation and most plant miRNAs, triggering mRNA cleavage. Here, using polysome fractionation in Arabidopsis thaliana, we found that a portion of mature miRNAs and ARGONAUTE1 (AGO1) is associated with polysomes, likely through their mRNA target. We observed enhanced accumulation of several distinct miRNA targets at both the mRNA and protein levels in an ago1 hypomorphic mutant. By contrast, translational repression, but not cleavage, persisted in transgenic plants expressing the slicing-inhibitor 2b protein from Cucumber mosaic virus. In agreement, we found that the polysome association of miR168 was lost in ago1 but maintained in 2b plants, indicating that translational repression is correlated with the presence of miRNAs and AGO1 in polysomes. This work provides direct biochemical evidence for a translational component in the plant miRNA pathway.